Analisis Peran Organizer dalam Pelaksanaan Kegiatan Employee Gathering Bandara Soekarno-Hatta - Evelyn Tahar; Firman Syah (Bisnis Event, 2023)
An employee gathering, known as one of the effective methods in human resource management, can strengthen relationships among employees, boost motivation, and celebrate shared achievements. This study focuses on the Employee Gathering at Soekarno-Hatta Airport as a form of appreciation for the Main Branch Office employees at Soekarno-Hatta Airport for their achievements in 2022, as well as a tool to enhance performance. This research explores the crucial role of organizers in managing employee gathering activities to achieve desired goals. The research methodology involves direct observation of the Employee Gathering activities at Soekarno-Hatta Airport and interviews with relevant parties. The research findings indicate that the role of organizers has a significant impact on the successful implementation of employee gathering activities.